Toll-Like Receptors 2 and 4 Cooperate in the Control of the Emerging Pathogen Brucella microti - Arias, Maykel A.; Santiago, Llipsy; Costas-Ramon, Santiago; Jaime-Sánchez, Paula; Freudenberg, Marina; Jiménez De Bagüés, Maria P.; Pardo, Julián (Frontiers in Cellular and Infection Microbiology, 2017)
Toll-like receptors (TLRs) recognise pathogen-derived molecules and play a critical role during the host innate and adaptive immune response. Brucella spp. are intracellular gram-negative bacteria including several virulent species, which cause a chronic zoonotic infection in a wide range of mammalian hosts known as brucellosis. Recently it was isolated from wild rodents a new Brucella species, Brucella microti, that was found to be pathogenic in mice. Using this species-specific model, it was previously found that CD8+ T cells are required to control this infection. In order to find out the role of TLR-mediated responses in the control of this pathogen, the course of infection of B. microti was analyzed over 3 weeks in wild-type (WT) and TLR knock out (KO) mice including TLR2-/-, TLR4-/-, TLR9-/-, TLR2x4-/- and TLR 2x4x9-/-. WT and single TLR2, TLR4 and TLR9 KO mice similarly control infection in liver and spleen. In contrast, bacterial clearance was delayed in TLR2x4-/- and TLR2x4x9-/- mice at 7 and 14 days post-infection. This defect correlated with impaired maturation and pro-inflammatory cytokine production in B. microti-infected dendritic cells from TLR2x4-/- and TLR2x4x9-/- mice. Finally, it was found that Tc cells from TLR2x4-/- and TLR2x4x9-/- mice showed reduced ability to inhibit growth of B. microti in macrophages, suggesting the involvement of TLR2 and 4 in the generation of specific Tc cells. Our findings indicate that TLR2 and TLR4 are required to control B. microti infection in mice and that this effect could be related to its participation in the maturation of dendritic cells and the generation of specific CD8+ Tc cells. □